Effects of racism on the socio-emotional wellbeing of Aboriginal Australian children - D. M. Macedo; L. G. Smithers; R. M. Roberts; Y. Paradies; L. M. Jamieson (BMC, 2019)
Abstract Background Racism is a pervasive experience in the life of Aboriginal Australians that begins in childhood. As a psychosocial stressor, racism compromises wellbeing and impacts developmental trajectories. The purpose of the present study was to estimate the effect of racism on indicators of Australian Aboriginal child socio-emotional wellbeing (SEWB) at one to two years after exposure. Age-related differences in the onset of symptoms were explored. Methods Data from the B- and K-cohorts of the Longitudinal Study of Indigenous Children were used (aged 6 to 12 years). Racism, confounding variables, and the Strengths and Difficulties Questionnaire (a measure of SEWB) were collected by questionnaires and guided interviews with each child's main caregiver. Adjusted Poisson regression was used to estimate the relative risk (RRa) effects of racism on SEWB for both cohorts separately. RRa were pooled in a random effects meta-analysis. Results Exposure to racism was associated with an adjusted point estimate indicating a 41% increased risk for total emotional and behavioural difficulties, although the confidence intervals were wide (pooled RRa 1.41, 95% CI 0.75, 2.07). Analyses by cohort showed younger children had higher RRa for total difficulties (RRa 1.72, 95% CI 1.16, 2.54), whilst older children had higher RRa for hyperactive behaviour (RRa 1.66, 95% CI 1.01, 2.73). Conclusions The effects observed contributes to our understanding of the impact of racism on Aboriginal Australian children. Support for emotional and behavioural difficulties, and hyperactive behaviour, for Aboriginal children might help counteract the effects of racism. Future longitudinal research and policies aimed at reducing racism in Australian society are necessary.